(untitled) (Delito y Sociedad, 2021)
Stigma, from the contributions of Erving Goffman, is an attribute and is recently considered a social process. Interactionist perspective in sociology states that stigma can be deployed in various areas of social interaction and converge on other social phenomena such as discrimination and violence. In addition, the stigma belongs to specific social groups, among which are convicts and ex-convicts. Such a group is clearly devalued and rejected by society. Through a documentary review, this work seeks to analyze and understand the effects of this particular group’s stigma on the Mexican context. Although empirical research on the causes and effects of stigma on men and women is lacking, it has been found that in Mexico there is a homogeneous profile for convicts, who, inside and outside the prison, live in conditions of stigma, violence and discrimination, which has structural causes such as poverty, inequality and social exclusion. For women, the stigma is gender-related. Finally, a relationship is established between the experiences of stigma and discrimination within the prison and the difficulties faced by individuals after being released.